PENGARUH PROFITABILITAS, CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Wisnu Febryanzah Prasetyo; Abubakar Arif (Jurnal Ekonomi Trisakti, 2022)
This study aims to analyze the influence of profitability, corporate social responsibility, leverage, dan capital intensity on tax avoidance in manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. The data used are secondary data consist of company’s financial report and sustainability report. This study is a quantitative study with data testing carried out by descriptive statistical analysis, panel data regression model test, classical assumption test and hypothesis test. By using purposive sampling, there are 11 companies that are used based on predefined criteria with a total of 55 samples. The data analysis use multiple linier regression. The results of this study showed that the leverage have significant positive effect on tax avoidance; profitability have significant negative effect on tax avoidance; corporate social responsibility and capital intensity have no significant effect on tax avoidance.